Embracing Culinary Tourism as a Strategy for Boosting Regional Development: Bangka Belitung Case Studies - Levyda, Levyda; Giyatmi, Giyatmi; Ratnasari, Kania; Valeriani, Devi (Integrated Journal of Business and Economics (IJBE), 2024)
Both regional and national growth are aided by culinary tourism. Every region needs to have an appropriate strategy in place to compete with the others in order to maximize development. Creating a supply-demand-driven culinary tourism strategy is the aim of this study. Hybrid technique was employed in this investigation. Participants in this study included chefs, tour operators, owners of agricultural tourism firms, local government representatives in the tourism sector, and operators of restaurants and hotels. SWOT analysis was conducted using the results of visitor surveys, aerial observations, focus group discussion, and secondary data. Suggested course of action: Priority plans are selected by government officials and executives of travel industry associations, and AHP is used to process them. Product, pricing, marketing communication, and collaboration are the recommended areas of concentration. To increase price competitiveness, culinary products from upstream to downstream must work together. Among the goods that must be created are facilities, culinary festivals and events, culinary-related activities, and organizations dedicated to culinary tourism. Collaborative marketing communications are needed to maximize culinary tourism-related media and messaging. There are restrictions on research involving horizontal stakeholders. Future research needs to look at the various ways that stakeholders collaborate.